The Impact of the Covid-19 Pandemic and the Lockdown on the Health and Living Conditions of Undocumented Migrants and Migrants Undergoing Legal Status Regularization - Burton-Jeangros, Claudine; Duvoisin, Aline; Lachat, Sarah; Consoli, Liala; Fakhoury, Julien; Jackson, Yves (Frontiers in Public Health, 2020)
Introduction Undocumented migrants are at high risk of adverse consequences during crises because of a lack of access to essential securities and sources of support. This study aims to describe the impact of the COVID-19 crisis on the health and living circumstances of precarious migrants in Switzerland and to assess whether those undergoing legal status regularization fared better than undocumented migrants. Materials and methods This cross-sectional mixed methods study was conducted during the COVID-19 lockdown in April - May 2020. Undocumented and recently regularized migrants taking part in an ongoing cohort study were asked to respond to an online questionnaire. A subsample was selected to undergo semi-directed phone interviews. Results Overall, 117 of the 379 (30.9%) cohort study participants responded to the questionnaire. Seventeen interviews were conducted. Migrants faced cumulative and rapidly progressive difficulties in essential life domains. As a consequence, they showed high prevalence of exposure to COVID-19, poor mental health along with frequent avoidance of health care. Moreover, the loss of working hours and the related income overlapped with frequent food and housing insecurity. Around one participant in four had experienced hunger. Despite these unmet needs, half of the participants had not sought external assistance for reasons that differ by legal status. Both groups felt that seeking assistance might represent a threat for the renewal or a future application for a residency permit. While documented migrants were less severely affected in some domains by having accumulated more reserves previously, they also frequently renounced to sources of support. Conclusions The cumulated difficulties faced by migrants in this period of crisis and their limited search for assistance highlight the need to implement trust-building strategies to bridge the access gap to sources of support along with policies protecting them against the rapid loss of income, the risk of losing their residency permit and the exposure to multi-fold insecurities.